Emergency admission and survival from aggressive non-Hodgkin lymphoma: A report from the UK's population-based Haematological Malignancy Research Network. (June 2017) - Kane, Eleanor; Howell, Debra; Smith, Alexandra; Crouch, Simon; Burton, Cathy; Roman, Eve; Patmore, Russell
Abstract: Background: Non-Hodgkin lymphoma (NHL) is often diagnosed after emergency presentation, a route associated with poor survival and an indicator of diagnostic delay. Accounting for around half of all NHLs, diffuse large B-cell lymphoma (DLBCL) is of particular interest since although it is potentially curable with standardised chemotherapy it can be challenging to identify at an early stage in the primary care setting. Patients and methods: Set within a socio-demographically representative United Kingdom population of around 4 million people, data are from an established patient cohort. This report includes all patients (≥18 years) diagnosed with DLBCL 2004–2011 (n = 1660). Emergency admissions were identified via linkage to Hospital Episode Statistics using standard methods, and survival was examined using proportional hazards regression. Results: Two out of every five patients were diagnosed following an emergency admission, and this was associated with advanced disease and poor survival (p < 0.001). Among the 80% of patients treated with curative chemotherapy, survival discrepancies emerged at the point of diagnosis; the adjusted hazard ratio (emergency versus non-emergency) at one month being 4.0 (95% confidence interval 1.9–8.2). No lasting impact was evident in patients who survived for 12 months or more. Conclusion: Emergency presentation impacts negatively on DLBCL survival; patients presenting via this route have significantly poorer outcomes than patients with similar clinical characteristics who present via other routes. Highlights: Emergency presentation has a marked impact on non-Hodgkin lymphoma (NHL) survival, not explained by disease stage or treatment. Emergency presentation among patients with diffuse large B-cell lymphoma is 50% higher in the United Kingdom than national data on non-Hodgkin lymphomas suggest. Survival benefits from earlier diagnosis of potentially curable NHLs could exceed that of new treatments.